Challenging Hegemony Through Narrative: Centering Women's Experiences and Establishing a Sis-Science Culture Through a Women-Only Doping Forum. (August 2022) - Andreasson, Jesper; Henning, April
Understandings of image and performance enhancing drugs (IPEDs) and their use has largely been conceptualized through the lens of male hegemonic patterns, treating women's doping as a threat to the "natural" gender order. This article focuses on an exclusive, women-only online IPED forum. It aims to describe and analyze how this new forum was met within the broader doping community, and how issues related to IPED use and gender are addressed by women when their views are not backgrounded by potential male commentators and misogynistic discourses. The results show that first-hand knowledge is disseminated by women, which contributes to the foundation of a women's ethnopharmacological (sub)culture. Women, their bodies, and experiences become the standard and the "unspoken" norm in the discussions. The secluded space allows women to challenge patterns of hegemonic masculinity, while building and reinforcing women's experiences, bodies, and expertise as the standard. This stresses the importance of moving beyond hegemonic conceptualizations to understand the ongoing socio-cultural changes to the gender balance of IPED use and to center women's doping experiences, and the risks associated with use. This has implications for the formation and development of both this community and of a "sis-science" based on women's knowledge and experience.